Potential Number of Passenger and Performance Evaluation of Surabaya School Bus - Adhi Muhtadi; Sapto Budi Wasono; Hitapriya Suprayitno; Ervina Ahyudanari (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2019)
Surabaya school bus is one of public facilitiesassetsand itsperformance should be evaluated periodically. Because the school bus is a public asset, it necessary to process the facility asset management to maintain operational performance optimally and efficiently. The number of students who use the school bus declines from year to year. Therefore, it’s necessary to study the current performance of school buses and the number of potential students who can use the Surabaya school bus. The method used to survey the number of students utilizing school buses and to conduct school bus performance research. School bus itinerary starts from Dukuh Menanggal Street down to Dharmahusada Indah Street and back to Dukuh Menanggal Street. There are 43 schools along the school buses route. Travel time observed was 1 hour and 10 minutes. The load factoraverage of the 1stschool bus in segment 1 (Dukuh Menanggal - RSI) is 78.67% while in segment 2 (RSI - SMKN 5) it reaches 96%. The load factoraverage of 2nd school bus for segment 1 reach 31.33% and for segment 2 reach only 8%.The total number of students from 11 schools was 12,391 students. However, the number of passengers/day was only 38 students from the operational of two school buses. This indicates that many students were still reluctant to use school buses, so that school bus performance improvements are needed to attract high school and junior high school students.